Perbedaan Jarak Molar Kedua Ke Ramus Mandibula Akibat Konsistensi Makanan (Kajian radiograf panoramik di Instalasi Radiologi Dental Rumah Sakit Gigi dan Mulut Fakultas Kedokteran Gigi Universitas Trisakti) - Vivian Vivian; Rosalina Tjandrawinata; M. Novo Perwira Lubis (Fakultas Kedokteran Gigi Universitas Trisakti, 2019)
Background: One of the affected factor to the distance of second molar to ramus of the mandible is environment. Environment factor that has the closest correlation with the distance of second molar to ramus of the mandible is the consistency of food. The aim of this study was to find the differences of the distance between distal surface of second molar to ramus of the mandible based on food consistency. Materials and Methods: The sample consisted of 41 female and 33 male, between 19 to 30 years old, who consume hard consistency food or soft consistency food divided using questionnaire. The samples had complete teeth up to the second molar, which were reviewed from panoramic radiograph. Results: Data analysis shows that there is differences in the distance of second molar distal to ramus of the mandible based on food consistency, which average value is 10.38 mm for the male who consume hard food consistency and 7.35 mm for the male who consume soft food consistency. Conclusions: The average value for the female who consume hard food consistency is 9.21 mm while the value is 5.72 mm for female who consume soft food consistency.